The Financial Burden of Out-of-Pocket Expenses in the US and Canada: How Different is the US? - Katherine Baird (Luxembourg Income Study (LIS), 2016)
Background: This paper compares the burden medical cost-sharing requirements place on households in the US and Canada. It estimates and the probability that individuals with similar demographic features in the two countries have large medical expenses relative to income. Method: We use 2010 nationally-representative household survey data harmonized for crossnational comparisons to identify individuals with high medical expenses relative to income. Using logistic regression, we estimate the probability of high expenses occurring among ten different demographic groups in the two countries. Results: The results show the risk of large medical expenses in the US is one and a half to four times higher than it is in Canada, depending on the demographic group and spending threshold used. The US compares least favorably when evaluating poorer citizens, and when a higher spending threshold is used. Conclusions: Recent health care reforms can be expected to reduce Americans' catastrophic health expenses, but it will take very large reductions in out-of-pocket expenditures - larger than can be expected - if poorer and middle class families are to have the financial protection from high health care costs that their counterparts in Canada have.
Keywords: 330